Nilai Ekonomi Sadranan Perspektif Masyarakat Bukan Pengguna Melestarikan Budaya Sadranan - Sri Walyoto (Jurnal Ilmiah Ekonomi Islam, 2019)
The purpose of this study was to determine the value of the Cepogo sadranan cultural tradition from the perspective communities to form Non Use Value . Non Use Value is value a combination of opsyen values, existence, heritance that forms Passive value. The research was conducted on the community not users in Central Java. The Contingent Valuation Method (CVM) was used in this study. Multiple linear models are used to find out the variables studied are and explained by independent variables (distance, income, age). The results of the study of the independent variables significantly can explain the variables studied the willingness of the community not the user to pay (WTP) to preserve the cultural tradition of Cepogo sadranan. An organization that manages sadranan culture preservation funds is needed so that the understanding of future generations can still preserve the sadranan cultural tradition as a vehicle for unifying community friendship.